Practice of endoscopy during COVID-19 pandemic: position statements of the Asian Pacific Society for Digestive Endoscopy (APSDE-COVID statements). Issue 6 (2nd April 2020) - Chiu, Philip Wai Yan; Ng, Siew C; Inoue, Haruhiro; Reddy, D Nageshwar; Ling Hu, Enqiang; Cho, Joo Young; Ho, Lawrence KY; Hewett, David G; Chiu, Han-Mo; Rerknimitr, Rungsun; Wang, Hsiu-Po; Ho, Shiaw Hooi; et al.
Abstract : Coronavirus-19 (COVID-19) caused by SARS-CoV-2 has become a global pandemic. Risk of transmission may occur during endoscopy and the goal is to prevent infection among healthcare professionals while providing essential services to patients. Asia was the first continent to have a COVID-19 outbreak, and this position statement of the Asian Pacific Society for Digestive Endoscopy shares our successful experience in maintaining safe and high-quality endoscopy practice at a time when resources are limited. Sixteen experts from key societies of digestive endoscopy in Asia were invited to develop position statements, including patient triage and risk assessment before endoscopy, resource prioritisation and allocation, regular monitoring of personal protective equipment, infection control measures, protective device training and implementation of a strategy for stepwise resumption of endoscopy services after control of the COVID-19 outbreak.